Analysis on Drivers' Vision-psychology under the Influence of Color Difference after Pavement Pothole Repair - Hongjun Jing* (Faculty of Mechanical Engineering in Slavonski Brod, Faculty of Electrical Engineering in Osijek, Faculty of Civil Engineering in Osijek, 2021)
Pavement pothole repair, as one of the commonest methods used in routine road maintenance works, is effective to extend the pavement service life and increase its transport capacity. However, there are significant color differences between the old and new pavements after pothole repair, and there are few studies about the impact of color differences on driving safety. Thus, using multiple typical pavements with the pothole repair, we aim to reveal the impact of the color differences between the old and new materials on the driving safety, and to improve the safety and comfort of drivers. Tobii eye tracker and the ErgoLAB physiological recorder were used to test the driver's visual parameters when the vehicles run under the pothole repair environment, including drivers' gaze frequency, gaze duration, saccade range and heart rate variability. Results show that the color differences of the road after pothole repair have a significant influence on the drivers' vision and psychology, resulting in reduced driving safety and stability. Compared with the unrepaired road section, the gaze frequency and duration of drivers on pothole sections are significantly increased. The speed of saccade is also increased, and the saccade range is reduced. Meanwhile, the average heart rate of drivers on the pothole sections is increased by 10-20%, indicating that drivers' attention and heart rate fluctuate greatly when passing through potholes, which can easily cause emotional tension and misjudgment, and thereby reduce the safety of driving. The obtained conclusions provide a significant reference for subsequent research.